Analysis of the Relationship Between the Degree of Dysbiosis in Gut Microbiota and Prognosis at Different Stages of Primary Hepatocellular Carcinoma - Ni, Jiajia; Huang, Rong; Zhou, Huifang; Xu, Xiaoping; Li, Yang; Cao, Peihua; Zhong, Kebo; Ge, Mei; Chen, Xiaoxia; Hou, Baohua; Yu, Min; Peng, Baogang; et al. (Frontiers in Microbiology, 2019)
Gut microbiota dysbiosis is closely associated with primary hepatocellular carcinoma (HCC). Recent studies have evaluated the early diagnosis of primary HCC through analysis of gut microbiota dysbiosis. However, the relationship between the degree of dysbiosis and the prognosis of primary HCC remains unclear. Because primary HCC is accompanied by dysbiosis and dysbiosis usually increases the circulatory concentrations of endotoxin and other harmful bacterial substances, which further increases liver damage, we hypothesized that level of dysbiosis associated with primary HCC increases with the stage of cancer progression. To test this hypothesis, we introduced a more integrated index referred to as the degree of dysbiosis (Ddys); and we investigated Ddys of the gut microbiota with the development of primary HCC through high-throughput sequencing of 16S rRNA gene amplicons. Our results showed that compared with healthy individuals, patients with primary HCC showed increased pro-inflammatory bacteria in their fecal microbiota. The Ddys increased significantly in patients with primary HCC compared with that in healthy controls. Moreover, there was a tendency for the Ddys to increase with the development of primary HCC, although no significant difference was detected between different stages of primary HCC. Our findings provide important insights into the use of gut microbiota analysis during the treatment of primary HCC.